OVERVIEW AND EMPIRICAL STATISTICAL ANALYSIS OF THE IMPACT OF SPIRITUALISM FOR ENHANCING THE PERFORMANCE OF MANAGERS IN CORPORATE SECTOR (Singaporean Journal of Business Economics and Management, 2020)
The impact of Spiritualism in enhancing the Performance of the Business Managers in Corporate Sector has been empirically discussed in the present paper. The significance of the concepts of 5 Cs i.c. Communications, Collaboration, Commitment, Creativity and Compassion; and 3Ps i.e. People, Planet, and Profit in this study, has been discussed in detail. The importance of Spiritual Transactions and Ethical Assets has been highlighted. An empirical mathematical formula for evaluating the impact of Spiritualism in increasing the Performance Efficiency has been suggested. The paper is expected to be useful for the Academicians and Researchers engaged in studies of Spiritualism in Business World.